N-doped carbon coated porous hierarchical MnO microspheres as superior additive-free anode materials for lithium-ion batteries. (1st April 2022) - Hong, Ye; Hu, Qianqian; Dong, Haiyong; Li, Jianhong; Tang, Zilong; Wang, Xiaojun; Ouyang, Jian; Liu, Ting
Abstract: Novel N-doped carbon coated porous hierarchical MnO microspheres have been successfully synthesized via the simultaneous pyrolysis of MnCO3 and polyacrylonitrile (PAN) at low calcination temperature. The micro/nano structure with uniform N-doped carbon coating, suitable interior pores and tiny primary MnO nanocrystals can significantly increase the electronic conductivity of the composite, reduce the amount of irreversible solid-electrolyte interphase (SEI) layer, accommodate the huge volume change of MnO during cycling and facilitate easier redox reaction of Mn 2+ /Mn x + ( x >2) to generate extra capacity. By using partially pyrolytic PAN as the conductive agent and binder, the obtained additive-free MnO-based electrode (MnO@NC-S) demonstrates a high reversible capacity of 998 mAh g −1 after 100 cycles at 0.1 A g −1 and remarkable long-term cycling stability with the capacity of 629 mAh g −1 after 500 cycles at 0.5 A g −1 . Graphical abstract: Image, graphical abstract